Edible aquatic Coleoptera of the world with an emphasis on Mexico - Moreno José; Ramos-Elorduy Julieta; Camacho Victor (BMC, 2009)
Abstract Anthropoentomophagy is an ancient culinary practice wherein terrestrial and aquatic insects are eaten by humans. Of these species of insects, terrestrial insects are far more commonly used in anthropoentomophagy than aquatic insects. In this study we found that there are 22 genera and 78 species of edible aquatic beetles in the world. The family Dytiscidae hosts nine genera, Gyrinidae one, Elmidae two, Histeridae one, Hydrophilidae six, Haliplidae two and Noteridae one. Of the recorded species, 45 correspond to the family Dytiscidae, 19 to Hydrophilidae, three to Gyrinidae, four to Elmidae, two to Histeridae, four to Haliplidae and one to Noteridae. These beetles are the most prized organisms of lentic watersThe family that has the highest number of edible food insect genera and species is Dytiscidae. Here, the global geographic distribution of species in these organisms is shown, and a discussion is presented of its importance as a renewable natural resource widely used for food in various countries.